If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -1x = 4x + 6 Reorder the terms: -6 + -1x = 6 + 4x Solving -6 + -1x = 6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -6 + -1x + -4x = 6 + 4x + -4x Combine like terms: -1x + -4x = -5x -6 + -5x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 -6 + -5x = 6 + 0 -6 + -5x = 6 Add '6' to each side of the equation. -6 + 6 + -5x = 6 + 6 Combine like terms: -6 + 6 = 0 0 + -5x = 6 + 6 -5x = 6 + 6 Combine like terms: 6 + 6 = 12 -5x = 12 Divide each side by '-5'. x = -2.4 Simplifying x = -2.4
| 15=b-a | | 6t+9t=80 | | 20+3b=20 | | 3x^2+15x+27= | | 9x+5y=-35 | | -5x-5=3x+11 | | 234*n=6 | | (-3x^4p^7)(6y^5x^3)= | | 8a^2b^2-32ab= | | z+25=y | | x-7(x-4)=30-5x | | 5-.6x=-6 | | 6x^10+24x^9+48x^8+7x^6+28x^5+56x^4+3x^2+12x+24=0 | | 7w+23=4w+8w-22 | | A(10)=3+(10-1)(7) | | 2x-5(x-2)=-3+4x-36 | | -15+2=18 | | 6(n-9)=n-19 | | 3x=5x-34 | | A(10)=3+(10-1)(+7) | | -25+k=12 | | y=cos^2(7x) | | A(10)=15+(10-1)(-5) | | (4x+3)-(x-4)-4x(4)=x | | 3x-7y=10x+14z | | 8r=11r | | 9x-3=4x-9 | | 24.50+x=36.50 | | x*13+23=x*5+159 | | 28(3c+4)=2(c+6)+c | | -4x-2=34 | | -7u-2=5 |